Flight Dynamics Of A Coaxial Compound Helicopter With Rotor-On-Rotor Interactional Aerodynamics - Jun, D.; Juhasz, O.; Cocco, A.; Saetti, U. (My University, 2024)
This paper focuses on the integration of a generalized rotor-on-rotor interactional aerodynamics model in state-variable form within a flight dynamics simulation and on its subsequent linearization and linear model analysis. The aircraft chosen for this investigation is a generic lift-offset compound coaxial rotorcraft. Upon trimming the flight dynamics at hover, linearized models of the dynamics are compared to nonlinear simulations, and with baseline models that do not account for rotor-on-rotor inflow interference effects. Model-order reduction methods are investigated to guide the development of linearized models that are tractable for flight control design while still predicting the effect of rotor-on-rotor interactions on the vehicle flight dynamics. It is found that, at hover and for the coaxial configuration in consideration, rotor-on-rotor interactions result in a lower magnitude of the rolling/pitching moment to lateral/longitudinal velocity derivative and in a lower roll/pitch damping derivative. These changes in stability derivatives yield roll and pitch subsidence modes at a lower frequency and roll and pitch oscillation modes with a higher natural frequency. The resulting frequency responses show a reduction in the magnitude of the roll response to on axis inputs (approximately 0.7 to 10 rad/s). In forward flight, the dominant effect is at low frequencies in the pitch axis. These findings are in line with previous studies focusing on flight-test data based model validation of the Sikorsky X2TDTM.